Reconciling emissions trading and the promotion of renewable energy - Sebastian Schäfer (Philipps-University Marburg, School of Business and Economics, 2018)
The EU emissions trading system (ETS) and the promotion of renewable energy are overlapping regulations. Although the resulting early development of renewables is associated with several advantages such an overlap may violate the path of optimal abatement. Subsidies may cause a too high share of renewables in electricity generation. This results in additional expenses and efficiency losses. We develop a control mechanism serving as thumb rule to limit additional expenses. Under optimal implementation the rule significantly restricts additional expenses to a maximum of about 4% of total abatement costs in worst case. This result holds for marginal abatement costs (MAC) approximated by any conical combination of weak convex power functions. This means high flexibility of MAC leading to high validity of the results. Consequences of a non-optimal implementation of the mechanism are examined as well. An empirical application to German data shows that the promotion of renewable energy has not yet violated the path of optimal abatement. However, data is restricted because the ETS has not induced an additional emission reduction since 2010.
Keywords: D61; H23; Q42; Q48; Q54; 330; Overlapping Regulations; Promotion of Renewable Energy; Emissions Trading